Integrating the Youth into Aquaculture project in Southern Africa - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Edith Gondwe, Management Trainee, NEPAD Regional Fish Node speaks about the Fish for Youth programme in Southern Africa. The Forum for Agricultural Research in Africa (FARA) in collaboration with the Government of Ghana will convene the 6th Africa Agriculture Science Week from July 15-19 in Accra, a continental gathering of all stakeholders involved in African agriculture. Learn more: http://www.cgiar.org/calendar-events/ http://www.fara-africa.org/scienceweek/